Essays. - Liverani, Mario, author.
1 online resource (cccxxiv, 14 pages).
Keywords: In this volume, Niels Peter Lemche and Emanuel Pfoh present an anthology of seminal studies by Mario Liverani, a foremost scholar of the Ancient Near East. This collection contains 18 essays, 11 of which have originally been published in Italian and are now published in English for the first time. It represents an important contribution to Ancient Near Eastern and Biblical Studies, exposing the innovative interpretations of Liverani on many historical and ideological aspects of ancient society. Topics range from the Amarna letters and the Ugaritic epic, to the 'origins' of Israel. Historiography, Ideology and Politics in the Ancient Near East and Israel will be an invaluable resource for Ancient Near Eastern and Biblical scholars, as well as graduate and post-graduate students.